Epidermal Growth Factor Receptor: A Potential Therapeutic Target for Diabetic Kidney Disease - Sheng, Lili; Bayliss, George; Zhuang, Shougang (Frontiers in Pharmacology, 2021)
Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease worldwide and the major cause of renal failure among patients on hemodialysis. Numerous studies have demonstrated that transient activation of epidermal growth factor receptor (EGFR) pathway is required for promoting kidney recovery from acute injury whereas its persistent activation is involved in the progression of various chronic kidney diseases including DKD. EGFR-mediated pathogenesis of DKD is involved in hemodynamic alteration, metabolic disturbance, inflammatory response and parenchymal cellular dysfunction. Therapeutic intervention of this receptor has been available in the oncology setting. Targeting EGFR might also hold a therapeutic potential for DKD. Here we review the functional role of EGFR in the development of DKD, mechanisms involved and the perspective about use of EGFR inhibitors as a treatment for DKD.